Genome-Wide Association Mapping to Identify Genetic Loci for Cold Tolerance and Cold Recovery During Germination in Rice - Thapa, Ranjita; Tabien, Rodante E.; Thomson, Michael J.; Septiningsih, Endang M. (Frontiers in Genetics, 2020)
Low temperature significantly affects rice growth and yield. Temperatures lower than 15°C are generally detrimental for germination and uniform seedling stand. To investigate the genetic architecture underlying cold tolerance during germination in rice, we conducted a genome-wide association study using a novel diversity panel of 257 rice accessions from around the world and the 7K SNP marker array. Phenotyping was conducted in controlled growth chambers under dark conditions at 13°C. The rice accessions were measured for low-temperature germinability, germination index, coleoptile length under cold stress, plumule length at 4 d recovery, and plumule length recovery rate. A total of 51 QTLs were identified at a p < 0.001 and 17 QTLs were identified using an FDR < 0.05 across the different chilling indices with the whole panel of accessions. At the threshold of p < 0.001, a total of 20 QTLs were identified in the subset of Japonica japonica accessions, while 9 QTLs were identified in the subset of Indica indica accessions. Considering the recurring SNPs and linked SNPs across different chilling indices, we identified 31 distinct QTL regions in the whole panel, 13 QTL regions in the Japonica japonica subset, and 7 distinct QTL regions in the Indica indica subset. Among these QTL regions, 3 regions were common between the whole panel and Japonicajaponica, 3 regions were common between the whole panel and Indicaindica, and 1 region was common between Indica indica and Japonicajaponica. A subset of QTL regions was potentially colocalized with previously identified genes and QTLs, including 10 from the Japonica japonica subset, 4 from the Indica indica subset, and 6 from the combined panel. On the other hand, a total of 21 potentially novel QTL regions from the combined panel, 10 from the Japonica japonica subset, and 1 from the Indica indica subset were identified. The results of our study provide useful information on the genetic architecture underlying cold tolerance during germination in rice, which in turn can be used for further molecular study and crop improvement for low-temperature stressed environments.